1980
DOI: 10.1139/x80-088
|View full text |Cite
|
Sign up to set email alerts
|

Potential hazard rating system for fir stands infested with budworm using cambial electrical resistance

Abstract: Cambial electrical resistance (CER) of more than 10 000 trees, predominantly balsam fir (Abiesbalsamea) and red spruce (Picearubens) was measured in 90 stands in northern Maine, New Hampshire, and Vermont, U.S.A. CER index values (mean CER, kiloohms per stand) ranged from 9 to 13 for fir in nonoutbreak situations, and 9 to 18 in outbreak situations with moderate to heavy budworm infestation, whereas values for red spruce remained essentially constant at 7 to 13 in both situations. Balsam fir trees in stands wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…CER was significantly lower in trees in limed plots indicating that these trees had a wider cambial zone and, hence, faster growth rate than trees in the unlimed plots. CER measurements in balsam fir showed that trees with a CER of 9 kΩ or less grew three times faster than trees with a CER of 13 kΩ (Davis et al 1980). Subsequent work with balsam fir indicated that CER was related to the width or number of vascular cambial cells in the current growth ring (Smith et al 1984) and the concentration of mobile ions, principally K in the cambial zone (Blanchard et al 1983) CER also reflected the beneficial effects of liming on foliar-and soil-element content.…”
Section: Cambial Electrical Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…CER was significantly lower in trees in limed plots indicating that these trees had a wider cambial zone and, hence, faster growth rate than trees in the unlimed plots. CER measurements in balsam fir showed that trees with a CER of 9 kΩ or less grew three times faster than trees with a CER of 13 kΩ (Davis et al 1980). Subsequent work with balsam fir indicated that CER was related to the width or number of vascular cambial cells in the current growth ring (Smith et al 1984) and the concentration of mobile ions, principally K in the cambial zone (Blanchard et al 1983) CER also reflected the beneficial effects of liming on foliar-and soil-element content.…”
Section: Cambial Electrical Resistancementioning
confidence: 99%
“…CER was used as a stand hazard index for rating vulnerability of balsam fir (Abies balsamea L.) to damage from spruce budworm (Davis et al 1980) and also was useful in separating red spruce stands into classes of low, intermediate, and high vigor and vitality (Smith and Ostrofsky 1993). In studies with sugar maple, CER did not distinguish crown condition classes in urban trees but was correlated with visual crown symptoms in a nonurban setting (Newbanks and Tattar 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The use of electrical methods for the tapid evaluation of the growth potential of trees has been studied in balsam fir {Abies balsamea L.) in the northeastern United States, where outbreaks of sprtice budwomi {Choiistoneura fumiferana Clem.) have eaused serious defoliation and mortality (DAVIS et al 1980). As the cambial electrical resistance (CER) increased, periodic growth decreased.…”
Section: Introductionmentioning
confidence: 99%
“…In several species of conifers and broadleaf trees, cambial electrical resistance (CER) measured during the growing season was related to radial growth (SHORTLE et al 1977(SHORTLE et al , 1979DAVIS et al 1980;BLANCHARD et al 1983;SHORTLE 1985;LINDBERG and JOHANSSON 1989;OSTROFSKY and SHORTLE 1989). The relationship of CER to ring width in balsam fir (Abies balsamea L.) was linked to the thickness of the vascular cambial zone (VCZ) during the growing season (BLANCHARD et al 1983;SMITH et al 1984).…”
Section: Introductionmentioning
confidence: 99%